Phospholipid:Diacylglycerol Acyltransferase1 Overexpression Delays Senescence and Enhances Post-heat and Cold Exposure Fitness - Demski, Kamil; Łosiewska, Anna; Jasieniecka-Gazarkiewicz, Katarzyna; Klińska, Sylwia; Banaś, Antoni (Frontiers in Plant Science, 2020)
In an alternative pathway to acyl-CoA:diacylglycerol-acyltransferase (DGAT)-mediated triacylglycerol (TAG) synthesis from diacylglycerol, phospholipid:diacylglycerol acyltransferase (PDAT) utilises not acyl-CoA but an acyl group from sn-2 position of a phospholipid, to form TAG. The enzyme’s activity in vitro matches DGAT’s in a number of plant species, however its main function in plants (especially in vegetative tissue) is debatable. In the presented study, we cultivated PDAT1-overexpressing, pdat1 knockout and wild-type lines of Arabidopsis thaliana through their whole lifecycle. PDAT1 overexpression prolonged Arabidopsis lifespan in comparison to wild-type plants, whereas knocking out pdat1 accelerated the plant’s senescence. After subjecting the three-week old seedlings of the studied lines (grown in vitro) to two-hour heat stress (40 ℃) and then growing them for one more week in standard conditions, the difference in weight between wild-type and PDAT1-overexpressing lines increased in comparison to the difference between plants grown only in optimal conditions. In another experiment all lines exposed to two-week cold stress experienced loss of pigment, except for PDAT1-overexpressing lines, which green rosettes additionally weighed 4 times more than wild-type. Our results indicate that plants depleted of PDAT1 are more susceptible to cold exposure, while PDAT1 overexpression grants plants a certain heat and cold resilience. Since it was shown, that lysophospholipids may be intertwined with stress response, we decided to also conduct in vitro assays of acyl-CoA:lysophosphatidylcholine acyltransferase (LPCAT) and acylCoA:lysophosphatidylethanolamine acyltransferase (LPEAT) activity in microsomal fractions from the PDAT1-overexpressing Arabidopsis lines in standard conditions. The results show significant increase in LPEAT and LPCAT activity in comparison to wild-type plants. PDAT1-overexpressing lines’ rosettes also present twice as high expression of LPCAT2 in comparison to control. The presented study shows how much heightened expression of PDAT1 augments plant condition after stress and extends its lifespan.